Mabādi' al-'Āmmah sebagai Kerangka Epistemologis bagi Ekoteologi Al-Qur'an: Nalar Integratif Ali Jum'ah - Moh Soim (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2026)
The escalating global environmental crisis has intensified scholarly interest in religious approaches that offer ethical and theological foundations for ecological sustainability. Although Islamic environmental ethics has received growing attention, limited studies have examined how contemporary Qur'anic scholarship constructs an integrated epistemological framework for ecotheology. This study aims to analyze Ali Jum'ah's concept of Mabādi' al-'Āmmah as an epistemological framework for developing Qur'anic ecotheology. Employing a qualitative library research design with an analytical-critical approach, the study examines Ali Jum'ah's writings through thematic analysis of Qur'anic principles and their application to contemporary environmental issues. The findings demonstrate that Mabādi' al-'Āmmah functions as an integrative interpretive framework that systematically derives universal Qur'anic principles and translates them into theological, ethical, and social responsibilities toward the environment. Within this framework, tawḥīd serves as the ontological foundation of the human–nature relationship, khilāfah establishes ecological responsibility, and mīzān provides the ethical principle for maintaining environmental balance and justice. Consequently, Qur'anic ecotheology is understood not merely as environmental ethics but as a comprehensive spiritual paradigm in which environmental stewardship constitutes an integral expression of worship ('ibādah) and moral accountability before God. This study contributes to contemporary Qur'anic studies by conceptualizing Mabādi' al-'Āmmah as an epistemological framework for Qur'anic ecotheology, thereby enriching interdisciplinary discussions on Islam, environmental ethics, and sustainable ecological governance.